Peningkatan Kemampuan Menulis Cerpen Model Pembelajaran Snowball Throwing dengan Media Pita Asi - Sugiarti Sugiarti (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2018)
The purpose of this study was to improve the ability to write short stories through the Snowball Throwing learning model using Pita Asi media. The design used classroom action research with two cycles of activity. The subjects consisted of twenty nine students of class IX SMPN 4 Sampit. Initial observations show that the grade score for writing short stories by grade IX students is low 63.00. The collection of data on students' short story writing skills used a writing test. Selection of actions to improve students 'writing skills utilizing students' potential through the Snowball Throwing learning model with Pita Asi media. The data on the ability to write short stories were analyzed descriptively and quantitatively for each learning cycle. The results showed the students' ability to write short stories increased from the mean score = 63.00 (category less) at the initial observation to 73.